NBC : America's network - Hilmes, Michele, 1953-; Henry, Michael (Michael Lowell) (University of California Press, 2007)
Spanning eight decades from the beginnings of commercial radio to the current era of international consolidation and emerging digital platforms, this pioneering volume illuminates the entire course of American broadcasting by offering the first comprehensive history of a major network. Bringing together wide-ranging original articles by leading scholars and industry insiders, it offers a comprehensive view of the National Broadcasting Company (NBC) that brings into focus the development of this key American institution and the ways that it has intersected with, and influenced, the central even.